Risk factors of HIV-related oral lesions in adults - Maria Noel Marzano Rodrigues Petruzzi; Karen Cherubini; Fernanda Gonçalves Salum; Maria Antonia Zancanaro De Figueiredo (Universidade de São Paulo, 2013)
OBJECTIVE: To assess the risk factors in the occurrence of oral lesions in HIV-positive adults. METHODS: A retrospective analytical-descriptive survey was conducted using the medical/dental records of 534 patients with oral lesions associated with HIV. The data were collected from five referral centers for managing HIV and associated comorbidities in the city of Porto Alegre, Southern Brazil, between 1996 and 2011. Using a standardized form, socio-demographic and clinical data were recorded. Exclusively and definitively diagnosed oral pathologies were included and classified according to ECC criteria on Oral Problems Related to HIV Infection. For data analysis cross-tabulations, Chi-squared tests and logistic regression models were used where appropriate. RESULTS: CD4+ counts lower than 350 cells/mm³ (p < 0.001), alcohol consumption (p = 0.011) and female gender (p = 0.031) were predisposing factors for oral candidiasis. The occurrence of hairy leukoplakia was independently associated with CD4+ counts below 500 cells/mm³, (p = 0.029) a viral load above 5,000 copies/mm³ (p = 0.003) and smoking (p = 0.005). CONCLUSIONS: Moderate and severe degrees of immunodeficiency and detectable viral loads were risk factors for the onset of oral lesions. Smoking and alcohol consumption also increased susceptibility to the development of opportunistic infections in HIV-positive adults from Porto Alegre, irrespective of the use of antiretroviral therapy.